On Sulawesi Ceratina (Ceratinidia) (Hymenoptera, Apoidea, Anthophoridae). - Baker, Donald Burton (Contributions to Entomology = Beiträge zur Entomologie, 2002)
Ceratina (Ceratinidia) alexandrae and carinifrons, spp. nov., are described from Indonesia, Sulawesi.Keywordstaxonomy, biodiversity, agroecology, Indonesia.Nomenclatural Actsalexandrae Baker, 2002 (Ceratina), spec. n.carinifrons Baker, 2002 (Ceratina), spec. n.